2009
DOI: 10.1186/1471-2148-9-258
|View full text |Cite
|
Sign up to set email alerts
|

Genomic taxonomy of vibrios

Abstract: Background: Vibrio taxonomy has been based on a polyphasic approach. In this study, we retrieve useful taxonomic information (i.e. data that can be used to distinguish different taxonomic levels, such as species and genera) from 32 genome sequences of different vibrio species. We use a variety of tools to explore the taxonomic relationship between the sequenced genomes, including Multilocus Sequence Analysis (MLSA), supertrees, Average Amino Acid Identity (AAI), genomic signatures, and Genome BLAST atlases. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 63 publications
(76 reference statements)
9
145
0
1
Order By: Relevance
“…alginolyticus is closely related to V. parahaemolyticus and V. harveyi (Thompson et al, 2009). Recently, we determined the genomic sequence of the T3SS of V. alginolyticus ZJO strain (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…alginolyticus is closely related to V. parahaemolyticus and V. harveyi (Thompson et al, 2009). Recently, we determined the genomic sequence of the T3SS of V. alginolyticus ZJO strain (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Like most other Gram-negative pathogens, several Vibrio species, including Vibrio alginolyticus, Vibrio parahaemolyticus and Vibrio harveyi, also harbour gene clusters encoding a T3SS apparatus (Henke & Bassler, 2004;Makino et al, 2003;Thompson et al, 2009 , 2003). In fact, T3SS1 is required for the cytotoxicity of V. parahaemolyticus in HeLa cells, whereas T3SS2 is involved in its enterotoxicity in rabbit ileal loops (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The species description process needs to be automated and openly available to all, i.e., open access. Genomic taxonomy has already been successfully applied as an alternative for the more traditional species description and re-classification (Thompson et al 2009;Haley et al 2010;Thompson et al 2011aThompson et al , 2013bMoreira et al 2014a, b). For example, the genus Listonella was reclassified as a later heterotypic synonym of the genus Vibrio (Thompson et al 2011b), and a new taxonomic framework for the genus Prochlorococcus was proposed with the descriptions of new species (Thompson et al 2013c).…”
Section: Paradigm Shiftmentioning
confidence: 99%
“…Previous studies have demonstrated that multilocus sequencing analysis has a higher discriminatory power than DNA-DNA hybridization. 27,28 In fact, Thompson et al 29 have reported that when two Vibrio strains share more than 95% similarity by multilocus sequencing analysis, they are the same species. These results demonstrate that strain BFLP-10 T is distinct from any recognized species of the genus Vibrio.…”
Section: Phylogenetic Analysismentioning
confidence: 99%